Locating eloquent sites identified during brain tumor intraoperative mapping on reference MRI atlas - Angela Elia; Alexandre Roux; Clément Debacker; Sylvain Charron; Giorgia Simboli; Alessandro Moiraghi; Bénédicte Trancart; Edouard Dezamis; Jun Muto; Fabrice Chretien; Marc Zanello; Catherine Oppenheim; et al. (Communications Medicine)
Abstract Background Correlating the human connectome with clinical responses elicited during intraoperative brain mapping helps understanding of the intrinsic organization of the human brain. Methods for locating eloquent sites on neuroimaging are not standardized. In the present study, we standardized a methodology for locating subcortical eloquent sites identified during intraoperative mapping for awake brain tumor resection on a reference brain template. Methods Subcortical eloquent sites were tagged by co-registration of intraoperative photographs with early postoperative MRI ( < 48 h). Neuroimaging data were normalized into MNI152 space. To assess whether the location of subcortical eloquent sites on the MNI template was concordant with the expected brain connectivity, we compared each subcortical eloquent site with the Human Connectome Project 1065 probabilistic tractography atlas. Results We analyze 290 subcortical eloquent sites identified during 69/90 awake surgeries. 2/290 (0.7%) subcortical eloquent sites identified intraoperatively do not intersect with a fiber tract according to the reference atlas. Among the other 288 that successfully intersect with, at least, one white matter tract, 255/288 (88.5%) have a clinical response elicited intraoperatively that is congruent with the intersected white matter tract. In the remaining 33/288 (11.5%) functional incongruent and the 2/290 (0.7%) anatomical incongruent subcortical sites, the minimal mean distance between the eloquent site and a congruent with matter tract is 3.6 ± 4.4 mm (range 1.0–23.9, median 3.6, interquartile range 2.5–5.4). Conclusions We propose a standardized methodology to locate with accuracy on a reference brain template subcortical eloquent sites identified intraoperatively during functional brain mapping using direct electrical stimulations under awake condition.